Immunoregulation of autocrine prolactin: Suppressing the expression of costimulatory molecules and cytokines in T lymphocytes by prolactin receptor knockdown - Xu, Dongming; Lin, Ling; Lin, Xiahong; Huang, Ziyang; Lei, Zhenmin (Cellular immunology, 2010)
Ample evidence indicates that prolactin (PRL) secreted from the pituitary gland plays an important role in a variety of human immune responses. However, the immunoregulation of autocrine PRL in T lymphocytes is not fully understood. To evaluate the role of autocrine PRL in T lymphocyte activation, PRL receptor (PRLR) in Jurkat cells was silenced by lentivirus-mediated stable expression of PRLR shRNAi. Knockdown of PRLR resulted in a considerable reduction of phytohemagglutinin (PHA)-induced T cell proliferation. Moreover, the synthesis and secretion of CD137, CD154, IL-2 and IL-4 were significantly decreased, while the production of CD28, IFN-γ and IL-10 was not affected in PHA-primed PRLR-deficient cells. These results demonstrate the importance of autocrine regulation of the PRL signaling in T lymphocyte growth and activation, and support a mechanism by which autocrine PRL participates in the immunoregulation through selectively influencing the expression of certain critical costimulatory molecules and cytokines.